Determining brain death by EEG method activities of nurse-technician - Blagojević Dragana; Majstorović Danijel; Magdić Tamara; Teofilović Snežana (Association of Nurses Technicians and Midwives, 2015)
Brain death or electrocerebral silence (ESC) represents an irreversible loss of brain function, including the brain stem. The final diagnosis of brain death requires evidence that the brain, as an organ, has stopped functioning. One of the additional methods in determining brain death is electroencephalography (EEG). Role of a well-trained and competent EEG technician when registering electroencephalograph at patients in the possible state of brain death is very important and almost equally as important as the role of a professional interpreting that recording later.